안구건조증에서 눈물 내 기질 금속단백분해효소 9 검사 - 김동현 (검안 및 콘택트렌즈 학회지, 21(3), 2022)
안구건조증은 눈물막 이상과 안구 불편감을 특징으로 하며, 안구표면 염증이 주요 병인이다. 최근 InflammaDry라는 눈물 내 기질금속단백분해효소 9 검사(MMP-9)가 일상적인 임상 환경에서 안구건조증의 보조 진단 도구로 널리 사용되고 있다. 이 논문에서는안구건조증에서 MMP-9의 역할, InflammaDry 테스트 양성 소견과 안구건조증 증상 및 징후의 관계, 테스트 수행 시 특정 고려사항을살펴보고자 한다. Dry eye disease (DED) is a condition of the ocular surface characterized by tear film abnormalities and ocular symptoms; ocular surface inflammation is the principal pathogenesis. Recently, a matrix metalloproteinase-9 (MMP-9) point-of-care immunoassay (InflammaDry) has become widely used as an ancillary diagnostic tool in routine clinical settings. This paper reviews the role of MMP-9 in DED, the relationships of MMP-9-positivity on the InflammaDry test with the symptoms and signs of DED, and specific considerations when performing the test. KCI Citation Count: 0